Repositioning a product in the decline stage : Danonino case study - Tomás, Patrícia Alexandra Caetano (2017)
Through the analysis of a real repositioning case, the focus of this thesis is to assess the effectiveness of Danonino’s repositioning while understanding Danone’s strategy, the reasons behind this action, the steps taken and the reaction of both buyers and consumers to it. Danonino is the main children’s brand from Danone’s portfolio. This brand, suffered a repositioning strategy through packaging, portfolio and overall image in order to revert its negative cycle of sales , to boost Danone children's sector, differentiate from the competition, rise brand awareness and construct a positioning, taking several steps to achieve it. The main conclusions of this research, reveal that parents give a lot of importance to the nutritional benefits of yogurts and the flavor. However, price also plays an important decision role in parents’ buying behavior. For Children, the main decision drivers are the flavor, packaging and the convenience. By measuring buyers and consumer’s reactions, it was possible to conclude that Danonino is the brand that parents prefer in the majority of children’s yogurt categories where the brand is present. It was also possible to recognize the effectiveness of the repositioning strategy through the positive evolution of sales, penetration rate, brand awareness and preferences of parents and children regarding packaging.